Method for manufacturing powder material, paste material, and ceramic electronic component
By using nickel powder with controlled oxygen and sulfur ratios, the method addresses the challenges of maintaining electrode continuity and preventing cracks in ceramic electronic components, achieving high continuity rates.
Patent Information
- Application Number
- JP2021032057
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-01
- Publication Date
- 2024-12-18
- Estimated Expiration
- 2041-03-01
AI Technical Summary
Existing methods for producing thinner internal electrode layers in ceramic electronic components, such as multilayer ceramic capacitors, face issues with increased surface oxidation of nickel powder leading to binder removal cracks and deterioration of electrode continuity due to sulfur addition.
A nickel powder with specific oxygen and sulfur content ratios (0.042≦S/Sn weight ratio≦5.5, 0.39≦O/Sn weight ratio≦40) is used to maintain electrode continuity while suppressing cracks, combined with a manufacturing process that includes laminating dielectric and internal electrode layers.
The solution effectively maintains the continuity of internal electrode layers, preventing cracks and ensuring high continuity rates during the manufacturing process.
Smart Images

Figure 0007602306000002 
Figure 0007602306000003 
Figure 0007602306000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a powder material, a paste material, and a method for producing a ceramic electronic component. [Background technology]
[0002] Ceramic electronic components such as multilayer ceramic capacitors are manufactured by printing a metal paste made of metallic materials such as nickel (Ni) on a dielectric green sheet whose main raw material is a dielectric material such as barium titanate, and then laminating, pressing, cutting, debinding, firing, applying external electrodes, etc. In order to meet market demand for smaller and larger capacity ceramic electronic components, there is a demand for thinner internal electrode layers and higher lamination rates, as well as thinner dielectric layers. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2007-258646 A [Patent Document 2] JP 2014-5491 A Summary of the Invention [Problem to be solved by the invention]
[0004] To make the internal electrodes thinner, it is necessary to minimize the physical size of the metal powder particles before sintering (see, for example, Patent Document 1). However, when using base metal fine particles such as Ni, the amount of surface oxidation increases as the particle size decreases. In particular, when the surface oxide film is 2 mass% or more, the progress of binder removal due to surface oxygen cannot be ignored, and binder removal cracks frequently occur, which can be problematic.
[0005] It is known that sulfur (S) is added to suppress the reduction of surface oxygen (see, for example, Patent Document 2). However, if a large amount of S is added, a sudden contraction occurs when the S is desorbed, which causes cracks. In addition, the combustion reaction of S increases the degree of reduction in the atmosphere, accelerating the grain growth of the common material and dielectric, and deteriorating the continuity of the internal electrodes.
[0006] The present invention has been made in consideration of the above-mentioned problems, and aims to provide a powder material, a paste material, and a method for manufacturing a ceramic electronic component that can maintain the continuity rate of internal electrode layers while suppressing the occurrence of cracks. [Means for solving the problem]
[0007] The powder material according to the present invention comprises a Ni powder containing Sn and an S source, the amount of oxygen (O) in the Ni powder being 2 mass% or more relative to Ni, a weight ratio of S / Sn being 0.042≦S / Sn≦5.5, and a weight ratio of O / Sn being 0.39≦40.
[0008] In the above powder material, the oxygen in the Ni powder may be oxygen in a surface oxide of the Ni powder.
[0009] In the powder material, the amount of S relative to Ni may be 0.2 mass % or more.
[0010] In the above powder material, the Ni powder may have an average particle size of 0.01 μm to 0.2 μm.
[0011] The paste material according to the present invention comprises Ni powder containing Sn and an S source, the amount of oxygen (O) in the Ni powder being 2 mass% or more relative to Ni, the S / Sn weight ratio being 0.042≦S / Sn weight ratio being 5.5, and the O / Sn weight ratio being 0.39≦O / Sn weight ratio being 40.
[0012] In the above paste material, the oxygen in the Ni powder may be oxygen in a surface oxide of the Ni powder.
[0013] In the paste material, the amount of S relative to Ni may be 0.2 mass % or more.
[0014] In the above paste material, the Ni powder may have an average particle size of 0.01 μm to 0.2 μm.
[0015] A method for producing a ceramic electronic component according to the present invention includes the steps of: forming a laminate unit by forming an internal electrode pattern containing Ni powder containing Sn and an S source on a dielectric green sheet containing a ceramic material powder and an organic binder; laminating the laminate units to form a laminate; and firing the laminate, wherein the amount of oxygen (O) in the Ni powder is 2 mass% or more relative to Ni, 0.042≦S / Sn weight ratio≦5.5, and 0.39≦O / Sn weight ratio≦40.
[0016] In the above-described method for producing a ceramic electronic component, the oxygen in the Ni powder may be oxygen in a surface oxide of the Ni powder.
[0017] In the method for producing a ceramic electronic component, the amount of S relative to Ni may be 0.2 mass % or more.
[0018] In the above-described method for producing a ceramic electronic component, the Ni powder may have an average particle size of 0.01 μm to 0.2 μm. Effect of the Invention
[0019] According to the present invention, it is possible to provide a powder material, a paste material, and a method for manufacturing a ceramic electronic component that can maintain the continuity rate of internal electrode layers while suppressing the occurrence of cracks. [Brief description of the drawings]
[0020] [Figure 1] FIG. 2 is a partial cross-sectional perspective view of a multilayer ceramic capacitor. [Diagram 2] 2 is a cross-sectional view taken along line AA in FIG. 1. [Diagram 3] FIG. 2 is a cross-sectional view taken along line BB in FIG. [Figure 4] 1A to 1C are diagrams illustrating a flow of a method for manufacturing a multilayer ceramic capacitor. [Diagram 5] 1(a) and (b) are diagrams illustrating the lamination process. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] Hereinafter, an embodiment will be described with reference to the drawings.
[0022] (Embodiment) FIG. 1 is a partial cross-sectional perspective view of a multilayer ceramic capacitor 100 according to an embodiment. FIG. 2 is a cross-sectional view taken along line AA in FIG. 1. FIG. 3 is a cross-sectional view taken along line BB in FIG. 1. As illustrated in FIGS. 1 to 3, the multilayer ceramic capacitor 100 includes a laminated chip 10 having a substantially rectangular parallelepiped shape, and external electrodes 20a, 20b provided on any two opposing end faces of the laminated chip 10. Of the four faces of the laminated chip 10 other than the two end faces, the two faces other than the top and bottom faces in the stacking direction are referred to as side faces. The external electrodes 20a, 20b extend on the top, bottom and two side faces in the stacking direction of the laminated chip 10. However, the external electrodes 20a, 20b are spaced apart from each other.
[0023] The laminated chip 10 has a configuration in which dielectric layers 11 containing a ceramic material that functions as a dielectric and internal electrode layers 12 mainly composed of Ni (nickel) are alternately laminated. The edges of the internal electrode layers 12 are alternately exposed to the end face of the laminated chip 10 on which the external electrode 20a is provided and the end face on which the external electrode 20b is provided. As a result, each internal electrode layer 12 is alternately conductive to the external electrode 20a and the external electrode 20b. As a result, the laminated ceramic capacitor 100 has a configuration in which a plurality of dielectric layers 11 are laminated via the internal electrode layers 12. In addition, in the laminate of the dielectric layers 11 and the internal electrode layers 12, the internal electrode layers 12 are arranged on the outermost layer in the lamination direction, and the upper and lower surfaces of the laminate are covered by the cover layers 13. The cover layers 13 are mainly composed of a ceramic material. For example, the material of the cover layers 13 is the same as that of the dielectric layers 11 and the ceramic material.
[0024] The size of the multilayer ceramic capacitor 100 is, for example, 0.25 mm in length, 0.125 mm in width, and 0.125 mm in height, or 0.4 mm in length, 0.2 mm in width, and 0.2 mm in height, or 0.6 mm in length, 0.3 mm in width, and 0.3 mm in height, or 1.0 mm in length, 0.5 mm in width, and 0.5 mm in height, or 3.2 mm in length, 1.6 mm in width, and 1.6 mm in height, or 4.5 mm in length, 3.2 mm in width, and 2.5 mm in height, but is not limited to these sizes.
[0025] The dielectric layer 11 is mainly composed of a ceramic material having a perovskite structure represented by the general formula ABO3. 3-α For example, the ceramic material includes BaTiO3 (barium titanate), CaZrO3 (calcium zirconate), CaTiO3 (calcium titanate), SrTiO3 (strontium titanate), BaTiO3 (barium titanate) which forms a perovskite structure, 1-x-y Ca x Sr y Ti 1-z Zr zO3 (0≦x≦1, 0≦y≦1, 0≦z≦1), etc. can be used. The thickness of each dielectric layer 11 is, for example, 0.05 μm or more and 5 μm or less, or 0.1 μm or more and 3 μm or less, or 0.2 μm or more and 1 μm or less.
[0026] 2, a region where the internal electrode layer 12 connected to the external electrode 20a and the internal electrode layer 12 connected to the external electrode 20b face each other is a region that generates capacitance in the multilayer ceramic capacitor 100. Therefore, the region that generates capacitance is referred to as a capacitance region 14. In other words, the capacitance region 14 is a region where adjacent internal electrode layers 12 connected to different external electrodes face each other.
[0027] The region where the internal electrode layers 12 connected to the external electrode 20a face each other without an internal electrode layer 12 connected to the external electrode 20b being interposed therebetween is referred to as the end margin 15. The region where the internal electrode layers 12 connected to the external electrode 20b face each other without an internal electrode layer 12 connected to the external electrode 20a being interposed therebetween is also the end margin 15. In other words, the end margin 15 is a region where the internal electrode layers 12 connected to the same external electrode face each other without an internal electrode layer 12 connected to a different external electrode being interposed therebetween. The end margin 15 is a region that does not generate capacitance.
[0028] 3, in the laminated chip 10, the regions extending from the two side surfaces of the laminated chip 10 to the internal electrode layers 12 are referred to as side margins 16. That is, the side margins 16 are regions provided to cover the ends of the multiple internal electrode layers 12 stacked in the above-mentioned laminated structure that extend to the two side surfaces. The side margins 16 are also regions that do not generate electrical capacitance.
[0029] The dielectric layer 11 is formed by firing a dielectric material including a ceramic material powder, an organic binder, and the like. The internal electrode layer 12 is formed by firing a powder material including Ni powder, a paste material including a co-material, and the like. In order to make the internal electrode layer 12 thinner, it is required to make the physical size of the Ni powder particles for forming the internal electrode layer 12 as small as possible. However, when the Ni powder is made smaller in diameter, the surface area increases. As the surface area increases, the absolute amount of the surface oxide film of the Ni powder increases. When the amount of oxygen (O) relative to Ni in the Ni powder becomes 2 mass% or more, the oxygen promotes the oxidation of the binder of the dielectric material, promoting debinding, and debinding cracks occur frequently and can become a problem. Debinding cracks are cracks caused by shrinkage caused by the promotion of debinding. The amount of oxygen relative to Ni is the weight ratio of oxygen when Ni+O is 100 mass%.
[0030] It is known that sulfur (S) is added to the paste material to suppress the reduction of Ni powder. However, if the amount of S added to Ni is too large, rapid shrinkage occurs when S is released, and cracks occur. In addition, the combustion reaction of S increases the degree of reduction in the atmosphere, accelerating the grain growth of the co-material and ceramic material powder, and the continuity of the internal electrode layer 12 may also deteriorate.
[0031] Therefore, in this embodiment, a powder material or paste material capable of maintaining the continuity of the internal electrode layers 12 while suppressing the occurrence of cracks is used.
[0032] First, a description will be given of a method for manufacturing the multilayer ceramic capacitor 100. FIG 4 is a diagram illustrating a flow of the method for manufacturing the multilayer ceramic capacitor 100.
[0033] (Raw powder production process) First, a dielectric material for forming the dielectric layer 11 is prepared. The A-site elements and B-site elements contained in the dielectric layer 11 are usually contained in the dielectric layer 11 in the form of a sintered body of ABO3 particles. For example, BaTiO3 is a tetragonal compound having a perovskite structure and exhibits a high dielectric constant. This BaTiO3 can generally be obtained by synthesizing barium titanate by reacting a titanium raw material such as titanium dioxide with a barium raw material such as barium carbonate. Various methods have been known so far as a method for synthesizing the main component ceramic of the dielectric layer 11, such as a solid-phase method, a sol-gel method, a hydrothermal method, and the like. In this embodiment, any of these methods can be adopted.
[0034] A predetermined additive compound is added to the obtained ceramic material powder according to the purpose. The additive compound may be an oxide of magnesium (Mg), manganese (Mn), vanadium (V), chromium (Cr), rare earth elements (yttrium (Y), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm) and ytterbium (Yb)), or an oxide containing cobalt (Co), nickel (Ni), lithium (Li), boron (B), sodium (Na), potassium (K) or silicon (Si), or a glass containing cobalt, nickel, lithium, boron, sodium, potassium or silicon.
[0035] For example, a compound containing an additive compound is wet mixed with a ceramic material powder, and then dried and pulverized to prepare a ceramic material powder. For example, the ceramic material powder obtained as described above may be pulverized as necessary to adjust the particle size, or may be combined with a classification process to adjust the particle size. Through the above steps, a dielectric material is obtained.
[0036] (Lamination process) Next, an organic binder such as polyvinyl butyral (PVB) resin, an organic solvent such as ethanol or toluene, and a plasticizer are added to the obtained dielectric material and wet mixed. The obtained slurry is used to coat a dielectric green sheet 52 on a substrate 51 by, for example, a die coater method or a doctor blade method, and then dried. The substrate 51 is, for example, a PET (polyethylene terephthalate) film.
[0037] Next, as illustrated in FIG. 5(a), a paste material for forming the internal electrode layer 12 is printed on a dielectric green sheet 52 to form an internal electrode pattern 53. In FIG. 5(a), as an example, four layers of internal electrode patterns 53 are formed on the dielectric green sheet 52 at predetermined intervals. The dielectric green sheet 52 on which the internal electrode patterns 53 are formed is taken as a lamination unit. The paste material may contain ceramic particles as a common material. The main component of the ceramic particles is not particularly limited, but is preferably the same as the main component ceramic of the dielectric layer 11. For example, BaTiO3 with an average particle size of 50 nm or less may be uniformly dispersed.
[0038] Next, while peeling off the dielectric green sheet 52 from the base material 51, the lamination units are laminated as exemplified in FIG. 5(b). Next, a predetermined number of cover sheets (e.g., 2 to 10 layers) are laminated on the top and bottom of the laminate obtained by laminating the lamination units, and are thermocompression bonded, and cut to a predetermined chip size (e.g., 1.0 mm×0.5 mm). In the example of FIG. 5(b), cutting is performed along the dotted lines. The cover sheet may have the same components as the dielectric green sheet 52, or may have a different additive compound.
[0039] (Firing process) The ceramic laminate thus obtained was subjected to binder removal treatment in a N2 atmosphere, after which a metal paste that would become the undercoat layers of the external electrodes 20a and 20b was applied thereto by a dipping method, and the ceramic laminate was then subjected to a dipping treatment in a nitrogen atmosphere under an oxygen partial pressure of 10 -5 ~10 -8 The laminated ceramic capacitor 100 is thus obtained, and is then fired in a reducing atmosphere of 1 atm at 1100 to 1300° C. for 10 minutes to 2 hours.
[0040] (Reoxidation treatment process) After that, a re-oxidation treatment may be performed at 600°C to 1000°C in an N2 gas atmosphere.
[0041] (Plating process) Thereafter, the external electrodes 20a, 20b may be coated with a metal such as Cu, Ni, Sn, etc. by plating. Through the above steps, the multilayer ceramic capacitor 100 can be manufactured.
[0042] (Composition of paste material) In this embodiment, in order to increase the lamination density of the internal electrode layers 12, the internal electrode layers 12 are thinned. For example, the thickness of each internal electrode layer 12 is 1 μm or less, 0.4 μm or less, or 0.2 μm or less. In order to thin the internal electrode layers 12, Ni powder having a small diameter is used as the Ni powder contained in the paste material for forming the internal electrode layers 12. For example, the average particle diameter of the Ni powder is 0.01 μm to 0.2 μm, 0.03 μm to 0.15 μm, or 0.05 μm to 0.11 μm.
[0043] When the diameter of the Ni powder is reduced, the surface area of the Ni powder increases. Accordingly, the absolute amount of the surface oxide film of the Ni powder increases. In this embodiment, Ni powder having an oxygen content of 2 mass% or more is used. This makes it possible to use Ni powder having a sufficiently small particle size, and the continuity rate of the internal electrode layer 12 after firing can be maintained at a high value.
[0044] In order to suppress the oxidation of the binder caused by oxygen contained in the Ni powder, the paste material contains a S source, which suppresses the reduction of the Ni powder, suppresses the oxidation of the binder, and suppresses the occurrence of cracks.
[0045] The Ni powder also contains a Sn source. A Sn source may be added separately to the Ni fine particles, or a Ni-Sn alloy powder may be used as the Ni powder. The addition of Sn forms a stable sulfide containing Sn with respect to the Ni sulfide, suppressing the combustion reaction of S and suppressing the rapid contraction caused by the rapid detachment of S. In addition, the increase in the reduction degree of the atmosphere is suppressed, and the grain growth of the ceramic material powder and the common material is suppressed. As a result, the continuity rate of the internal electrode layer 12 can be maintained at a high value.
[0046] If the amount of Sn in the paste material is too small relative to the amount of S, the combustion reaction of S may not be sufficiently suppressed. Therefore, in this embodiment, an upper limit is set for the S / Sn weight ratio. Specifically, the S / Sn weight ratio is set to ≦5.5.
[0047] If the amount of Sn relative to the amount of O in the paste material is too small, the progress of binder removal due to surface oxygen cannot be ignored, and there is a risk of binder removal cracks occurring. Therefore, in this embodiment, an upper limit is set for the O / Sn weight ratio. Specifically, the O / Sn weight ratio is set to ≦40.
[0048] If the amount of Sn in the paste material is too large, a liquid phase may appear in the internal electrode layer 12 during the firing process, causing the internal electrode layer 12 to become spherical, which may deteriorate the continuity rate of the internal electrode layer 12. Therefore, in this embodiment, a lower limit is set for the S / Sn weight ratio. Specifically, the S / Sn weight ratio is set to 0.042≦S / Sn weight ratio. Furthermore, a lower limit is set for the O / Sn weight ratio. Specifically, the O / Sn weight ratio is set to 0.39≦O / Sn weight ratio.
[0049] The paste material is obtained by adding additives to a powder material containing Ni powder. At the stage of the powder material, the following conditions may be satisfied: the amount of oxygen (O) in the Ni powder is 2 mass% or more relative to Ni, the S / Sn weight ratio is 0.042≦S / Sn weight ratio≦5.5, and the O / Sn weight ratio is 0.39≦O / Sn weight ratio≦40. In this case, the paste material after the additives are added to the powder material should also satisfy the above conditions. If the above conditions are not satisfied at the stage of the powder material, the components of the additives added to the powder material should be adjusted to satisfy the above conditions.
[0050] From the viewpoint of reducing the particle size of the Ni powder, the oxygen content in the Ni powder is preferably 2 mass % or more, and more preferably 2.5 mass % or more.
[0051] If the amount of oxygen in the Ni powder is too large, the progress of binder removal due to surface oxygen cannot be ignored, and binder removal cracks may occur. Therefore, it is preferable to set an upper limit on the amount of oxygen in the Ni powder. For example, the amount of oxygen in the Ni powder is preferably 5.5 mass% or less, more preferably 4 mass% or less, and even more preferably 3 mass% or less.
[0052] If the amount of S relative to Ni is small, there is a risk that the oxidation of the binder cannot be sufficiently suppressed. Therefore, it is preferable to set a lower limit for the amount of S relative to Ni. For example, the amount of S relative to Ni is preferably 0.2 mass% or more, and more preferably 0.3 mass% or more. The amount of S relative to Ni refers to the weight ratio of S when Ni+S is 100 mass%.
[0053] If the amount of S relative to Ni is too high, there is a risk of a large amount of S being desorbed. Therefore, it is preferable to set an upper limit on the amount of S relative to Ni. For example, the amount of S relative to Ni is preferably 0.6 mass% or less, more preferably 0.5 mass% or less, and even more preferably 0.4 mass% or less.
[0054] From the viewpoint of sufficiently suppressing the combustion reaction of S, the S / Sn weight ratio is preferably 5.5 or less, and more preferably 5 or less.
[0055] From the viewpoint of suppressing the occurrence of binder removal cracks, the O / Sn weight ratio is preferably 40 or less, and more preferably 30 or less.
[0056] From the viewpoint of suppressing the appearance of a liquid phase in the internal electrode layer 12, the S / Sn weight ratio is preferably 0.042 or more, and more preferably 0.08 or more, and the O / Sn weight ratio is preferably 0.39 or more, and more preferably 0.6 or more.
[0057] From the viewpoint of suppressing the combustion reaction of S, the amount of Sn relative to Ni is preferably 0.065 mass% or more, and more preferably 0.1 mass% or more. From the viewpoint of suppressing the appearance of a liquid phase in the internal electrode layer 12 during the firing process, the amount of Sn relative to Ni is preferably 11 mass% or less, and more preferably 6 mass% or less.
[0058] According to the manufacturing method of this embodiment, since the above-mentioned paste material is used, it is possible to maintain the continuity rate of the internal electrode layers while suppressing the occurrence of cracks.
[0059] In the above embodiments, a multilayer ceramic capacitor has been described as an example of a ceramic electronic component, but the present invention is not limited to this. For example, other electronic components such as a varistor or a thermistor may be used. EXAMPLES
[0060] The multilayer ceramic capacitor according to the embodiment was fabricated and its characteristics were examined.
[0061] (Examples 1 to 20 and Comparative Examples 1 to 31) Additives were added to the barium titanate powder, and the powder was thoroughly wet mixed and pulverized in a ball mill to obtain a dielectric material. A butyral-based organic binder, toluene and ethyl alcohol were added to the dielectric material as a solvent, and the dielectric green sheet was applied onto a PET substrate by the doctor blade method.
[0062] Next, an internal electrode pattern was formed on the dielectric green sheet by printing a conductive metal paste. The amount of surface oxide film of the Ni powder contained in the conductive metal paste was adjusted by synthesis conditions. In addition, the amount of S and the amount of Sn were adjusted by adding an S-containing dispersant and an Sn-containing organometallic complex solution at the paste preparation stage. In Example 1, the amount of surface oxygen relative to Ni was 2.30 mass%, the amount of S relative to Ni was 0.41 mass%, the amount of S relative to Ni was 0.10 mass%, the S / Sn weight ratio was 4.056, and the O / Sn weight ratio was 22.755. In Example 2, the amount of surface oxygen relative to Ni was 2.56 mass%, the amount of S relative to Ni was 0.34 mass%, the amount of S relative to Ni was 0.10 mass%, the S / Sn weight ratio was 3.364, and the O / Sn weight ratio was 25.328. In Example 3, the surface oxygen content of Ni was 3.98 mass%, the S content of Ni was 0.25 mass%, the Sn content of Ni was 0.10 mass%, the S / Sn weight ratio was 2.473, and the O / Sn weight ratio was 39.376. In Example 4, the surface oxygen content of Ni was 2.50 mass%, the S content of Ni was 0.55 mass%, the Sn content of Ni was 0.10 mass%, the S / Sn weight ratio was 5.441, and the O / Sn weight ratio was 24.734. In Example 5, the surface oxygen content of Ni was 3.71 mass%, the S content of Ni was 0.47 mass%, the Sn content of Ni was 0.10 mass%, the S / Sn weight ratio was 4.670, and the O / Sn weight ratio was 36.705. In Example 6, the surface oxygen content relative to Ni was 2.30 mass%, the S content relative to Ni was 0.41 mass%, the Sn content relative to Ni was 5.89 mass%, the S / Sn weight ratio was 0.070, and the O / Sn weight ratio was 0.391.In Example 7, the surface oxygen content relative to Ni was 2.56 mass%, the S content relative to Ni was 0.34 mass%, the Sn content relative to Ni was 5.89 mass%, the S / Sn weight ratio was 0.058, and the O / Sn weight ratio was 0.435.In Example 8, the surface oxygen content of Ni was 3.98 mass%, the S content of Ni was 0.25 mass%, the Sn content of Ni was 5.89 mass%, the S / Sn weight ratio was 0.042, and the O / Sn weight ratio was 0.676. In Example 9, the surface oxygen content of Ni was 2.50 mass%, the S content of Ni was 0.55 mass%, the Sn content of Ni was 5.89 mass%, the S / Sn weight ratio was 0.093, and the O / Sn weight ratio was 0.425. In Example 10, the surface oxygen content of Ni was 3.71 mass%, the S content of Ni was 0.47 mass%, the Sn content of Ni was 5.89 mass%, the S / Sn weight ratio was 0.080, and the O / Sn weight ratio was 0.630. In Example 11, the surface oxygen content relative to Ni was 2.50 mass%, the S content relative to Ni was 0.13 mass%, the Sn content relative to Ni was 0.10 mass%, the S / Sn weight ratio was 1.286, and the O / Sn weight ratio was 24.734. In Example 12, the surface oxygen content relative to Ni was 3.00 mass%, the S content relative to Ni was 0.01 mass%, the Sn content relative to Ni was 0.10 mass%, the S / Sn weight ratio was 0.099, and the O / Sn weight ratio was 29.681. Comparative Examples 1 to 31 are shown in Table 1. [Table 1]
[0063] The dielectric green sheets on which the internal electrode patterns were formed were stacked 470 times and fired in a reducing atmosphere. The shape of the stacked chip after firing was 1.0 mm x 0.5 mm x 0.5 mm. The thickness of the dielectric layer was 0.5 μm. The thickness of the internal electrode layer was 0.4 μm.
[0064] (analysis) Whether or not cracks occurred was examined for 200 samples for each of Examples 1 to 12 and Comparative Examples 1 to 31. For Examples 1 to 12 and Comparative Examples 1 to 31, if the crack occurrence frequency exceeded 1%, the crack judgment was judged to be failing (×), and if the crack occurrence frequency was 1% or less, the crack judgment was judged to be passing (◯).
[0065] The continuity ratio of the internal electrode layers of 200 samples was examined for each of Examples 1 to 12 and Comparative Examples 1 to 31. For Examples 1 to 12 and Comparative Examples 1 to 31, the continuity ratio was judged to be unsatisfactory (×) when the average continuity ratio of the internal electrode layers, which was calculated by observing the cross-sectional polished surface near the center of the chip with a SEM (scanning electron microscope) (magnification 2000 times, average of four fields of view), was less than 70%, was judged to be somewhat good (△) when the average continuity ratio was 70% or more but less than 80%, and was judged to be acceptable (◯) when the average continuity ratio was 80% or more.
[0066] In Comparative Examples 1 to 3, the continuity was judged to be unacceptable (×), which is believed to be because Ni powder with a small surface area (large average particle size) was used, so that the oxygen content of the Ni powder was less than 2 mass% relative to Ni.
[0067] In Comparative Examples 4 to 6, the continuity was judged to be pass (◯). This is believed to be because Ni powder with a large surface area (small average particle size) was used, so that the oxygen content of the Ni powder was 2 mass% or more relative to Ni. However, the cracks were judged to be fail (×). This is believed to be because the amount of oxygen was increased, which promoted binder removal, resulting in binder removal cracks.
[0068] The cracking evaluation was also judged to be unacceptable (×) in Comparative Examples 7 to 11. This is thought to be because, although the amount of S relative to Ni was 0.2 mass% or more, Sn was not added, and the combustion reaction of S was not suppressed, causing rapid shrinkage due to the rapid desorption of S.
[0069] The cracking evaluation was also judged to be unacceptable (×) in Comparative Examples 12 to 15. This is believed to be because, although the amount of S relative to Ni was 0.2 mass% or more, the amount of Sn added was small, so that the S / Sn weight ratio was not ≦5.5, the combustion reaction of S was not suppressed, and a sudden shrinkage occurred due to the sudden elimination of S.
[0070] The cracking judgment was also judged as failing (×) in Comparative Examples 16 to 20. This is thought to be because although the amount of S relative to Ni was 0.2 mass% or more, the amount of Sn added was small, so the O / Sn weight ratio was not ≦40, and the progress of binder removal due to surface oxygen could not be ignored, causing binder removal cracks to occur.
[0071] In Comparative Examples 21 to 24, the crack judgment was passed (◯). This is believed to be because the S combustion reaction was suppressed due to the increased amount of Sn added. However, the continuity judgment was failed (×). This is believed to be because the amount of Sn added was too large, the S / Sn weight ratio was not 0.042≦S / Sn weight ratio was not 0.39≦O / Sn weight ratio, and a liquid phase appeared during the firing process of the internal electrode layer 12.
[0072] The continuity ratio was also judged to be unacceptable (×) in Comparative Example 25. This is believed to be because the amount of Sn added was too large, the O / Sn weight ratio was not 0.39≦O / Sn weight ratio was not satisfied, and a liquid phase appeared during the firing process of the internal electrode layer 12.
[0073] The continuity ratio was also judged to be unacceptable (×) in Comparative Examples 26 and 27. This is believed to be because the amount of Sn added was too large, the S / Sn weight ratio was not 0.042≦ and the O / Sn weight ratio was not 0.39≦, and a liquid phase appeared during the firing process of the internal electrode layer 12.
[0074] The continuity ratio was also judged as unacceptable (×) in Comparative Examples 28 to 31. This is believed to be because the amount of Sn added was too large, and the S / Sn weight ratio did not satisfy 0.042≦S / Sn.
[0075] In contrast, the crack evaluation and the continuity evaluation were not evaluated as failures (×) in any of Examples 1 to 12. This is believed to be because, in the paste material, the oxygen content of the Ni powder was 2 mass% or more relative to Ni, the S / Sn weight ratio was 0.042≦S / Sn weight ratio ≦5.5, and the O / Sn weight ratio was 0.39≦O / Sn weight ratio ≦40.
[0076] Although the embodiments of the present invention have been described in detail above, the present invention is not limited to such specific embodiments, and various modifications and variations are possible within the scope of the gist of the present invention described in the claims. [Explanation of symbols]
[0077] 10 Stacked Chip 11 Dielectric layer 12 Internal electrode layer 13 Cover Layer 14 capacity area 15 End Margin 16 Side Margin 20a,20b external electrode 51 Base material 52 Dielectric green sheet 53 Internal electrode pattern 100 Multilayer ceramic capacitors
Claims
1. Ni powder containing Sn; and a source of S; The amount of oxygen (O) in the Ni powder is 2 mass% or more relative to Ni, 0.042≦S / Sn weight ratio≦5.5, A powder material characterized in that the O / Sn weight ratio is 0.39≦O / Sn≦40.
2. 2. The powder material according to claim 1, wherein the oxygen in the Ni powder is oxygen in a surface oxide of the Ni powder.
3. 3. The powder material according to claim 1, wherein the amount of S relative to Ni is 0.2 mass% or more.
4. 4. The powder material according to claim 1, wherein the Ni powder has an average particle size of 0.01 μm to 0.2 μm.
5. Ni powder containing Sn; and a source of S; The amount of oxygen (O) in the Ni powder is 2 mass% or more relative to Ni, 0.042≦S / Sn weight ratio≦5.5, A paste material characterized in that the O / Sn weight ratio is 0.39≦O / Sn≦40.
6. 6. The paste material according to claim 5, wherein the oxygen in the Ni powder is oxygen in a surface oxide of the Ni powder.
7. The paste material according to claim 5 or 6, characterized in that the amount of S relative to Ni is 0.2 mass% or more.
8. The paste material according to any one of claims 5 to 7, characterized in that the Ni powder has an average particle size of 0.01 µm to 0.2 µm.
9. forming an internal electrode pattern containing Ni powder containing Sn and an S source on a dielectric green sheet containing a ceramic material powder and an organic binder to form a laminate unit; forming a laminate by stacking the laminate units; and firing the laminate. The amount of oxygen (O) in the Ni powder is 2 mass% or more relative to Ni, 0.042≦S / Sn weight ratio≦5.5, A method for producing a ceramic electronic component, characterized in that an O / Sn weight ratio of 0.39≦O / Sn≦40.
10. 10. The method for producing a ceramic electronic component according to claim 9, wherein the oxygen in the Ni powder is oxygen in a surface oxide of the Ni powder.
11. 11. The method for producing a ceramic electronic component according to claim 9, wherein an amount of S relative to Ni is 0.2 mass % or more.
12. 12. The method for producing a ceramic electronic component according to claim 9, wherein the Ni powder has an average particle size of 0.01 μm to 0.2 μm.
Citation Information
Patent Citations
Laminated electronic component and method for manufacturing the same
JP2007258646A
Nickel powder and its manufacturing method, and conductive paste and multilayer ceramic electronic component using it
JP2008223068A
Nickel alloy powder and method for producing the same
JP2013170303A
Method for producing metal powder, metal powder, conductive paste and laminated ceramic electronic component
JP2014005491A
Multilayer ceramic electronic component and manufacturing method of the same
JP2020031202A
